Analysis and identification of the necroptosis landscape on therapy and prognosis in bladder cancer - Zhao, Zihan; Jiang, Ning; Zhang, Yulin; Bai, Yuhao; Liu, Tianyao; Li, Tianhang; Guo, Hongqian; Yang, Rong (Frontiers in Genetics, 2022)
Bladder cancer (BLCA) is one of the most common malignant tumors of the urinary system, but the current therapeutic strategy based on chemotherapy and immune checkpoint inhibitor (ICI) therapy cannot meet the treatment needs, mainly owing to the endogenous or acquired apoptotic resistance of cancer cells. Targeting necroptosis provides a novel strategy for chemotherapy and targeted drugs and improves the efficacy of ICIs because of strong immunogenicity of necroptosis. Therefore, we systemically analyzed the necroptosis landscape on therapy and prognosis in BLCA. We first divided BLCA patients from The Cancer Genome Atlas (TCGA) database into two necroptosis-related clusters (C1 and C2). Necroptosis C2 showed a significantly better prognosis than C1, and the differential genes of C2 and C1 were mainly related to the immune response according to GO and KEGG analyses. Next, we constructed a novel necroptosis-related gene (NRG) signature consisting of SIRT6, FASN, GNLY, FNDC4, SRC, ANXA1, AIM2, and IKBKB to predict the survival of TCGA-BLCA cohort, and the accuracy of the NRG score was also verified by external datasets. In addition, a nomogram combining NRG score and several clinicopathological features was established to more accurately and conveniently predict the BLCA patient’s survival. We also found that the NRG score was significantly related to the infiltration levels of CD8 T cells, NK cells, and iDC cells, the gene expression of CTLA4, PD-1, TIGIT, and LAG3 of TME, and the sensitivity to chemotherapy and targeted agents in BLCA patients. In conclusion, the NRG score has an excellent performance in evaluating the prognosis, clinicopathologic features, tumor microenvironment (TME), and therapeutic sensitivity of BLCA patients, which could be utilized as a guide for chemotherapy, ICI therapy, and combination therapy.